2007
DOI: 10.1021/jp0746446
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Study of the Influence of Host−Framework Flexibility on the Diffusion of Small Gas Molecules in One-Dimensional Zeolitic Pore Systems

Abstract: Molecular-dynamics simulations are performed to understand the role of host-framework flexibility on the diffusion of methane molecules in the one-dimensional pores of AFI-, LTL-, and MTW-type zeolites. In particular, the impact of the choice of the host model is studied. Dynamically corrected Transition State Theory is used to provide insights into the diffusion mechanism on a molecular level. Free-energy barriers and dynamical correction factors can change significantly by introducing lattice flexibility. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 50 publications
1
71
0
1
Order By: Relevance
“…[21] It was observed that gas molecules with a Lennard-Jones diameter larger than the time-averaged narrow sodalite windows can diffuse through the sodalite zeolite due to framework flexibility. [22,23] Also the flexibility of any bulky reaction intermediate implies a significant increase in conformational degrees of freedom that should be appropriately accounted for. [24] Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] It was observed that gas molecules with a Lennard-Jones diameter larger than the time-averaged narrow sodalite windows can diffuse through the sodalite zeolite due to framework flexibility. [22,23] Also the flexibility of any bulky reaction intermediate implies a significant increase in conformational degrees of freedom that should be appropriately accounted for. [24] Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…[21] It was observed that gas molecules with a Lennard-Jones diameter larger than the time-averaged narrow sodalite windows can diffuse through the sodalite zeolite due to framework flexibility. [22,23] Also the 5 flexibility of any bulky reaction intermediate implies a significant increase in conformational degrees of freedom that should be appropriately accounted for.[24] Intermediate C can also lead to byproduct D.In this paper we apply advanced molecular dynamics techniques, which, to some extent, allow capturing the framework flexibility, the presence of guest molecules and the occurrence of competitive reaction paths. This is done by means of two case studies, which are inspired by the MTO process.…”
mentioning
confidence: 99%
“…33,35,44 Several researchers have cautioned on the accuracy of the flexible model, showing that the diffusion coefficient is highly sensitive to the force field. 35,45 In comparing the rigid and flexible framework approaches, the influence of the force field can be partly factored out by using a time-averaged zeolite structure in the simulations. Krishna et al used this approach to study methane diffusion in several 8-ring 5 zeolites.…”
mentioning
confidence: 99%
“…45,55,56 Also, the introduction of Al and protons as well as the specific bridging Si-O-Al oxygens, differing from Si-O-Si oxygens, suggest that shell models might perform better. However, MD have traditionally preferred rigid ion force fields which behave much better in the usual MD algorithms in terms of energy conservation and computer time.…”
mentioning
confidence: 99%
“…En este sentido, un aspecto muy importante en el campo de la simulación molecular es la influencia de la flexibilidad de la red en la dinámica y, como consecuencia lógica de la flexibilidad de la red, la variación dinámica del tamaño de poro. Algunos estudios a este respecto pueden ser encontrados en la literatura, [81][82][83][84][85][86][87] aunque en ocasiones el factor de flexibilidad de la red no es tenido en cuenta. 88,89 El modelamiento dinámico de un sistema se hace imprescindible cuando se estudian fenómenos de transferencia de masa como la adsorción y difusión en materiales porosos.…”
Section: Campos De Fuerza Para El Estudio De Polimorfos Silíceosunclassified